The Satisfaction of service Social Security Hospital in Bangkok Metropolitan Region. - Rakyong, Chorphaka; Khongsawatkiat, Kittiphan (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The purpose of this research was to study the differences of demographic factors. The marketing mix factors and other factors, including reliability and positive attitude towards the authorities that affects satisfaction in social security hospital in Bangkok Metropolitan Region. The researcher has determined samples, set a sample size of 400 people by random sampling. The areas are divided into 6 zones and set the sample rate of 95 percent and a standard deviation ± 5 percent. The sample size consisted of 400 consumers who using and treatment in social security hospital. The Questionnaire was designed as instrument for data collection. Due to data analysis: descriptive statistics . For the hypothesis testing, inferential statistics were Independent t-test and One Way ANOVA at significant level of 0.05. The results of the independent study revealed that the majority of respondent were female, single status and age between 25-40 years old. The average monthly between 10,000-15,000 baht. The level of education was Bachelor’s degree. It takes less than 1 hour go to the hospital . Use more than 1 time per year. Mostly selected government hospital. The marketing mix factors, no increase expense .Emergency case could not to be cured immediately. And the authorities give a good advice information. The procedure was taking time more than 1 hour. The promotion should not expensive for medical checking up program. The location of hospital could be convenience for transportation. The consumer is reliability and a good attitude with the authorities . The physical characteristics of the hospital are inadequate to accommodate the service. The marketing mix should be adjusted in the event of an emergency to be treated immediately. The process should be quick. The promotion of health check has to a special price. The other factors are provided in good faith and a positive attitude towards the authorities . Article history : Accepted 9 August 2016 SIMILARITY INDEX = 2.48